A Case Report of Urethra Leiomyoma in a Young Woman - A.A Ketabchi; Gh Azizolahi; H Tabrizchi (Journal of Kerman University of Medical Sciences, 2007)
Leiomyoma of the female urethra is a rare condition and there have been only 35-40 reported cases in literature. We report a 20-year-old woman who had referred with a painless mass in her vaginal vestibule, dysparonia dysuria and previouse history of urine retention for two times. After clinical examination, imaging studies (US, MRI) and cystoscopy a mass in urethra protruding to vagina and bladder was diagnosed. She underwent biopsy and complete surgical resection. Histopathological study revealed urethral leiomyoma and after operation all symptoms disappeared.